Synthesis and Characterization of ZnO/CaO Nanocatalysts and Utilization in Biodiesel Transesterification Reaction from Waste Cooking Oil - Neristia Viky Marta; Amalia Putri Purnamasari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The increase in global energy demand has led to increased consumption of fossil fuels, resulting in increasingly depleted energy reserves. In addition, the use of fossil fuels has various negative environmental impacts, including air pollution, global warming, and greenhouse gas emissions. Therefore, the development of environmentally friendly, sustainable alternative energy sources is needed. One renewable energy source with development potential is biodiesel. This study aims to synthesize biodiesel from waste cooking oil through a transesterification reaction using ZnO/CaO nanocatalysts. The novelty of this research lies in the synthesis of ZnO/CaO nanocatalysts via a combination of sol-gel and impregnation methods, which are expected to increase the catalysts' surface area, stability, and catalytic activity. The CaO catalyst was synthesized using the sol-gel method and modified with ZnO through a wet impregnation method using Zn acetate precursor at various concentrations of 0%, 1%, 2%, and 3%. FTIR and XRD characterizations confirmed the success of ZnO impregnation on CaO, while PSA analysis showed a decrease in particle size from 107.85 nm on CaO to 79.28 nm on 1% ZnO/CaO, which has the potential to increase catalytic activity. The transesterification reaction was carried out at 65°C for 2 hours, using a methanol-to-oil molar ratio of 1:9 and a catalyst loading of 3% of the oil weight. The resulting biodiesel was then analyzed using GC-MS, and it was found that ZnO modification increased the methyl ester area percentage from 92.74% in CaO to 99.61% in ZnO/CaO 1%. In addition, the highest biodiesel yield using 1% ZnO/CaO produced a density of 853.8 kg/m³, a viscosity of 2.30 mm²/s (cSt), a water content of 0.02%, and an acid number of 0.43 mg-KOH/g.